PENGARUH KREATIVITAS DAN PENYESUAIAN DIRI SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII - Syanet Kontur; Patricia V.J. Runtu; Nicky Kurnia Tumalun (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the effect of creativity and self-adjustment of students on mathematics learning outcomes. The method in this study is a survey method. This research was conducted at SMP Negeri 2 Tondano in the even semester of the 2022/2023 academic year. The population in this study were all students of class VII from four classes with a total of 106 students. The sample in this study amounted to 68 students of class VII. Data collection techniques using a questionnaire. The variables of student creativity and adjustment were revealed by means of a questionnaire, and the results of learning mathematics were obtained from the grade VII student report cards for the even semester of the 2022/2023 academic year at SMP Negeri 2 Tondano. In this study Multiple Linear Regression Analysis is used to test the hypothesis. The results of the hypothesis test showed that creativity and self-adjustment of students had a positive effect on student learning outcomes of 47.3%. Based on the results of this study, it can be concluded that creativity and self-adjustment of students have a positive effect on student learning outcomes